Studies on Neotropical crickets: On the Hemigryllus Saussure, 1877 taxonomic placement (Orthoptera: Grylloidea), with comments on Gryllidae classification, including new species and records - Cadena-Castañeda, Oscar J. (Zootaxa, 2025)
The classification of the family Gryllidae and the composition of its subfamilies are commented, with special emphasis on the taxa from the Americas. As well, a key is provided for identifying Gryllidae subfamilies in the Neotropical region. The status of Hemigryllinae stat. rev. is restored as a subfamily, which only includes Hemigryllus, previously considered a tribe within Eneopterinae until now. Hemigryllinae stat. rev. and Hemigryllus are also redescribed, including an updated key for the species. The status of Hemigryllus ortonii is discussed, with a historical review of known records, which may belong to different species, while Hemigryllus kriechbaumeri stat. rev. is revalidated as the type species of the genus. Two new species are described: Hemigryllus gorochovi sp. nov. and Hemigryllus ankeri sp. nov. Additional specimens are also recorded for Hemigryllus woronovi and Hemigryllus columbi, with a precise locality for the latter being reported for the first time. Finally, the placement of Hemigryllinae stat. rev. within Gryllidae is discussed, as well as its adaptations for digging and swimming for its species.